THE EFFECT OF GIVING BREASTFEEDING ON BABY’S NUTRITIONAL STATUS: A COMPARATIVE STUDY IN NORTH BUTON DISTRICT, INDONESIA: EFFECT OF BREASTFEEDING - Tasnim, Tasnim (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2020)
Background: Mother who giving exclusive breast feeding in North Buton District was less than others in Nourt Buton District. This study investigated the risk factors of giving exclusive breastfeeding and non-exclusive breastfeeding for 0-6 month old babies’ nutritional status in Kulisusu primary health care in North Buton District.  Methods: This study was quantitative study which used a Case Control study design. Data analysis used independen t-test.  This study recruited 82 mothers who had under 6 months old babies. This study was conducted in Kulisusu Primary Health Care area, in North Buton, Southeast Sulawesi province, Indonesia.     Result: The resuld found that there was significant differences of nutritional  status between  babies who gave exclusive breastfeeding and non-exclusive breastfeeding for 0-6 months old babies (p value =0,001 < 0,05).  Conclusion: This study suggested for health workers and community health volunteers to give motivate for mothers in order to give exclusive breastfeeding for their babies aged under 6 months. The primary health care must promote about benefits of exclusive breastfeeding for babies’ health and their growth.